DESIGN AND FABRICATION OF EXHAUST GAS POWER GENERATION MACHINE - Omkar Mashalkar1, Vaibhav Londhe2, Rohit Chatage3; Ranjit Gidde; Narendra Narve (International Journal of Innovations in Engineering Research and Technology, 2022)
In this research work the modification of stationary engine for producing power using turbine. Nowadaysinautomobilefieldmanynewinnovatingconceptsarebeingdeveloped. We are using the power from vehicle exhaust to generate the electricity which can be stored in battery for the later consumption. In this project, wear demonstrating a concept of generating power in a stationary single cylinder diesel engine by the usage of turbines. Here we are placing a turbine in the path of exhaust inthe silencer. An engine is also placed in the chassis of the vehicle. The turbine is connected to a dynamo, which is used to generate power. Depending upon the airflow the turbine will start rotating, and then the dynamo will also start to rotate. A dynamo is a device which is used to convert the kinetic energy into electricaly.The generated power is stored to the battery.It can be stored in the battery after rectification. The rectified voltage can be inverted and can be used in various forms of utilities